Agents and multi-agent systems for health care : 10th International Workshop, A2HC 2017, São Paulo, Brazil, May 8, 2017, and International Workshop, A-HEALTH 2017, Porto, Portugal, June 21, 2017, Revised and extended selected papers /: 10th International Workshop, A2HC 2017, São Paulo, Brazil, May 8, 2017, and International Workshop, A-HEALTH 2017, Porto, Portugal, June 21, 2017, Revised and extended selected papers. (2017) - Unknown
No abstract available